Early dental implant failure: A review of the literature - Maria Cristina Leme Godoy dos Santos; Maria Isabela Guimarães Campos; Sergio Roberto Peres Line (Universidade Estadual de Campinas, 2015)
Osseointegrated dental implants have been considered the most esthetical and functional alternative to missing teeth. However, the treatment is not always successful resulting in the implant loss. The implant failure can be classified as early failure (the osseointegration is not established) and late failure (involving a breakdown of the established osseointegration). The implant loss can be attributed to factors such as biological, microbiological and biomechanical, but the cause and mechanism of the early implant failure are still obscure. The cluster phenomenon, multiple implant failures in the same subject, supports the evidence that individual characteristics play an important role in the early failure process. However, little is known about the influence of genetic susceptibility on osseointegration. The aim of this article was to present an evaluation of the literature regarding mechanism, epidemiology, histopathologic observations, role of inflammatory mediators and factors associated with early implant failures